ANALISIS PENERAPAN APLIKASI SI LAMTIM BERJAYA SEBAGAI WUJUD E-GOVERNMENT DALAM MENINGKATKAN PELAYANAN PUBLIK - Hikmah Nur Azizah; Edi Siswanto; Hermi Yanzi; Devi Sutrisno Putri; Febra Anjar Kusuma (STKIP Subang, 2026)
This study examines the implementation of the Si Lamtim Berjaya application as a form of e-government in improving public service delivery in East Lampung Regency. The problem addressed in this research is the suboptimal utilization of the application by the community despite its availability to facilitate administrative services. Therefore, this study aims to analyze the implementation of the application, assess community participation in its use, and identify the supporting and inhibiting factors affecting its optimization. This research employs a qualitative descriptive approach, with data collected through interviews, observations, and documentation involving government officials and community members. The data were analyzed using data reduction, data display, and conclusion drawing techniques, supported by source and method triangulation to ensure validity. The results indicate that the Si Lamtim Berjaya application has contributed positively to improving public services by enhancing accessibility, efficiency, and transparency. However, community participation remains uneven due to limited digital literacy, technical issues within the system, and persistent preferences for conventional service methods. Supporting factors include ease of access, time efficiency, and government socialization efforts. In conclusion, while the application demonstrates the potential of e-government in public service improvement, further optimization is required, particularly in strengthening digital literacy and system reliability to achieve more effective and inclusive service delivery.